Performance Enhancement of Double-Pass Solar Air Heater Using Phase Change Materials and Air Flow Turbulators - Suzah, Zainab Nadeem; J. Hamad, Ahmed; N. Khalifa, Abdul Hadi (Journal of engineering and sustainable development (Online), 2025)
In this study, two techniques to improve the thermal performance of the double-pass solar air heater are experimentally investigated. The first is integrating a phase change material (PCM) as a thermal storage system, and the second is using flow turbulators with the absorber plate to enhance the heat transfer in the solar air heater (SAH). Four different arrangements of the modified SAH absorber plate integrated with and without PCM and flow turbulators with used longitudinal fins on the plate's lower surface are investigated. The modified SAH was examined based on three air flow rates, 0.002, 0.005, and 0.012 kg/s, under Baghdad city climatic conditions. The results demonstrated that the modified double-pass SAH integrated with PCM had a higher performance than the conventional SAH. The outlet air temperature in modified cases 1, 2, and 3 was higher by about 22, 14, and 9%, respectively, compared with the conventional case of flat plate. The flow turbulator of V-shaped revealed optimal performance where the improvement in thermal efficiency was 35% compared with 26% and 19% for other flow turbulators cases 1, and 2, respectively. was observed that the use of PCM increased the operating time by 2 hours after the sunset.